A taxonomic review of the Margarodoid genus Stigmacoccus Hempel (Hemiptera: Sternorrhyncha: Coccoidea: Stigmacoccidae), with some details on their biology - Hodgson, Chris; Gamper, Heather; Bogo, Amauri; Watson, Gillian (Zootaxa, 2007)
Stigmacoccus is an unusual scale insect genus from Central and South America that has been little studied. It belongs to the family Stigmacoccidae within the archaeococcoid group of genera which used to comprise the family Margarodidae (Morrison, 1927) but which are now considered to represent at least 9 families. The present paper describes or redescribes the adult females, adult males, cyst stages and crawlers of the three known species (S. asper, S. garmilleri, and S. paranaensis), plus the prepupa of S. garmilleri and S. paranaensis, and (briefly), the pupa of S. paranaensis. It is considered that the female has two cyst stage instars; the number in the male is uncertain. Adult female S. asper and S. paranaensis appear to have groups of loculate pores on the walls of the vagina. A lectotype for S. asper is designated. In addition, cyst stages of three further undescribed species are described (but not formally named) and illustrated. Some observations on the biology and life cycle are also included. The honeydew of Stigmacoccus species has been shown to be an important energy source for overwintering passerine birds which defend this resource. A summary of our present knowledge is presented, including how the honedew is eliminated (through a long anal tube) and details are given with regard to rates of honeydew flow, sugar concentration, cyst densities and annual timing of peak flows. The annual life cycle, as far as it is known, is discussed. It is concluded that this honeydew could be economically important as a source of sugar for honey production but this would need to be carefully managed to maintain an ecological balance.